2022
DOI: 10.1021/acs.jpcc.2c05718
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Phase Sensitivity of 5-Hydroxymethylfurfural Hydrodeoxygenation over a Pt1Co Single-Atom Alloy Catalyst

Abstract: In reactions of hydrodeoxygenation (HDO) of biomass-derived chemicals, one promising method for improving the yield of desirable products is to control the crystal phase of the catalyst and thus the adsorption configuration of intermediates. In this work, we have investigated the catalytic activity and selectivity of Pt 1 Co single-atom alloy (SAA) catalysts with fcc (face-centered cubic) and hcp (hexagonal close-packed) cobalt crystal phases toward 5-hydroxymethylfurfural (5-HMF) HDO reaction by density funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In terms of non-noble metals, Lu et al prepared Co 1 @Mo/ NC with Co−N 4 sites by the coordinative pyrolysis method and subjected it to the HDO of HMF. The reaction offered a 77% DMF yield and a 28.7 h −1 TOF value under 2.0 MPa H 2 , 170 °C, and 8 h. 72 A synergistic effect between the Co and the Mo sites 74 The results showed that Pt 1 @ Co-hcp offered a higher catalytic performance than Pt 1 @Co-fcc in the production of DMTHF, originating from the different exposed crystal phases and atomic densities. It was demonstrated that the desirable product on the Pt 1 @Co-hcp surface was DMTHF, while that on the Pt 1 @Co-fcc surface was 2hexanol.…”
Section: Furanic Conversion 311 5-hydroxymethylfurfural (Hmf) Conversionmentioning
confidence: 94%
See 1 more Smart Citation
“…In terms of non-noble metals, Lu et al prepared Co 1 @Mo/ NC with Co−N 4 sites by the coordinative pyrolysis method and subjected it to the HDO of HMF. The reaction offered a 77% DMF yield and a 28.7 h −1 TOF value under 2.0 MPa H 2 , 170 °C, and 8 h. 72 A synergistic effect between the Co and the Mo sites 74 The results showed that Pt 1 @ Co-hcp offered a higher catalytic performance than Pt 1 @Co-fcc in the production of DMTHF, originating from the different exposed crystal phases and atomic densities. It was demonstrated that the desirable product on the Pt 1 @Co-hcp surface was DMTHF, while that on the Pt 1 @Co-fcc surface was 2hexanol.…”
Section: Furanic Conversion 311 5-hydroxymethylfurfural (Hmf) Conversionmentioning
confidence: 94%
“…Controlling the adsorption configuration of HMF on the catalyst surface provides a viable route to enable a mild conversion. Shi et al calculated the effect of Pt 1 @Co SAA with different cobalt crystal phases (face-centered cubic (fcc) and hexagonal close-packed (hcp)) on the HDO of HMF . The results showed that Pt 1 @Co-hcp offered a higher catalytic performance than Pt 1 @Co-fcc in the production of DMTHF, originating from the different exposed crystal phases and atomic densities.…”
Section: Application Of Sacs In Biomass Chemical Conversionmentioning
confidence: 99%
“…Recently, a DFT calculation analysis has revealed the crucial roles of the crystal phase of SACs on the reaction selectivity. 56 The optimal products were identified to be 2-hexanol and DHMF on Pt 1 Co-fcc (face-centered cubic) and Pt 1 Co-hcp (hexagonal tightly packed) catalysts, respectively. The crystal phase affects the adsorption configuration of the intermediates.…”
Section: (Hemi)cellulose-derived Feedstocksmentioning
confidence: 98%
“…Yawen Shi et al investigated the catalytic movement and separability Pt 1 Co-fcc and Pt 1 Co-hcp catalysts of Pt 1 Co single-atom composition metal (SAA) with fcc (face-centered cuboid) and hcp (hexagonal close-packed) cobalt crystalline stages for the HDO reaction of HMF, separately, by using density flooding theory (DFT) calculations. The best product on the Pt 1 Co hcp surface was DHMF, while the best product on the Pt 1 Co-fcc surface was 2-hexanol, comparing the reactivity and regioselectivity of the HDO reaction for HMF conversion on the Pt 1 Co-fcc and Pt 1 Co-hcp surfaces [33]. The work of Yawen Shi's team was successful in developing HDO catalysts with high performance by precise tuning of crystal phases.…”
Section: Precious Metalsmentioning
confidence: 99%